Prevalence and risk factors associated with wheezing in the first year of life - Costa Bessa, Olivia A. A.; Madeiro Leite, Alvaro J.; Sole, Dirceu [UNESP]; Mallol, Javier (Sociedade Brasileira de Pediatria, 2014)
Objective: to investigate the prevalence and risk factors associated with wheezing in infants in the first year of life.Methods: this was a cross-sectional study, in which a validated questionnaire (Estudio Internacional de Sibilancias en Lactantes - International Study of Wheezing in Infants - EISL) was applied to parents of infants aged between 12 and 15 months treated in 26 of 85 primary health care units in the period between 2006 and 2007. The dependent variable, wheezing, was defined using the following standards: occasional (up to two episodes of wheezing) and recurrent (three or more episodes of wheezing). The independent variables were shown using frequency distribution to compare the groups. Measures of association were based on odds ratio (OR) with a confidence interval of 95% (95% CI), using bivariate analysis, followed by multivariate analysis (adjusted OR [aOR]).Results: a total of 1,029 (37.7%) infants had wheezing episodes in the first 12 months of life; of these, 16.2% had recurrent wheezing. Risk factors for wheezing were family history of asthma (OR = 2.12; 95% CI: 1.76-2.54) and six or more episodes of colds (OR = 2.38; 95% CI: 1.91-2.97) and pneumonia (OR = 3.02; 95% CI: 2.43-3.76). For recurrent wheezing, risk factors were: familial asthma (aOR = 1.73; 95% CI: 1.22-2.46); early onset wheezing (aOR = 1.83; 95% CI: 1.75-3.75); nocturnal symptoms (aOR = 2.56; 95% CI: 1.75-3.75), and more than six colds (aOR = 2.07; 95% CI 1.43-.00).Conclusion: the main risk factors associated with wheezing in Fortaleza were respiratory infections and family history of asthma. Knowing the risk factors for this disease should be a priority for public health, in order to develop control and treatment strategies. (C) 2013 Sociedade Brasileira de Pediatria. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Prevalence; Risk factors; Cross-sectional studies; Infant